Persepsi Wisatawan Perempuan terhadap Implementasi Destinasi Ramah Lingkungan di Kabupaten Karangasem - Santi Diwyarthi, Ni Desak Made; Kusumarini, Indah; Citrawati, Luh Putu; Darmiati, Made; Mas Wiartha, Nyoman Gede (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research is a descriptive study with a quantitative approach. It aims to understand the perceptions of female tourists regarding the implementation of green tourism in Karangasem, Bali, particularly at Bias Tugel Beach, considering their significant role in family travel decision-making and their preferences for sustainability concepts. Data were collected through observation, questionnaires, and interviews with 100 female tourists visiting Bias Tugel Beach, Padang Bay District, Karangasem Regency, during the research period in August 2024. Analitical technique were quantitative description technique. Survey results showed that 45% of respondents highly considered environmental aspects when choosing a destination, with 27% preferring destinations with eco-friendly certifications, and 28% actively promoting environmental awareness. A total of 48% of respondents believed that accommodations in Karangasem had already implemented eco-friendly and sustainable principles, though 37% emphasized the need for improved training and skills for local human resources. Moreover, 52% of respondents regarded the preservation of local culture as an important aspect of their tourism experience, with 27% actively involved in cultural preservation efforts. Overall, female tourists in Karangasem exhibited a high level of awareness of green tourism principles and showed a strong preference for destinations that prioritize sustainability and cultural preservation. These findings are expected to support the development of more effective marketing and destination management strategies, positioning Karangasem as a leading destination for green tourism.